Copper content effects on the magnetic susceptibility profile of melt-quenched Bi1.6PboSr2Ca2CunOx superconducting ceramics - Natividad, Michelle T. (Animo Repository, 2007)
The melt-quenched method was applied in the fabrication of Bi1.6Pb0Sr2Ca2CunOx superconducting ceramics. The copper content, n, was varied from 2 to 3.5 in increments of 0.5. Characterization of the samples was done using the scanning electron microscope and energy dispersive spectroscope (SEM/EDAX), x-ray diffractometer (XRD) and magnetic susceptibility (x-T) analyses. The XRD patterns show that the low Tc (2212) phase is dominant in the samples with copper content, n = 2.0, 2.5 and 3.5 and the high Tc (2223) phase is dominant in the samples with n = 3.0. Magnetic susceptibility analyses show a one-step transition in the X-T highest transition temperature, Tc = 104K, was obtained from the sample with n = 3.0. The SEM images showed more enhanced crystal growth in the samples with n = 2.0 and 3.0. The n = 20 and n = 30 compositions were favorable in the growth of 2212 and 2223 phases respectively.